Theoretical Fracture Criterion of the Layered Elastic Composite Materials - Cilli, A. (AMER INST PHYSICS, 2016)
The theoretical fracture limit in compression of a composite material with two isotropic homogeneous elastic layers is studied using the piecewise homogeneous body model with the three-dimensional theory of elasticity. We assumed the layers have the initial local imperfections and these imperfections are moved with respect to each other by the same length which is expressed by the angle beta. The aim of the investigations was to study the influence of this length on the values of the theoretical fracture criterion limit. The numerical results for the influence of the initial local imperfections on the values of fracture limit are presented. It is therefore concluded that the values of the theoretical fracture limit increase with the length of the shifting.
Keywords: COMPRESSION; Physics